Effective Strategies in Developing Sustainable Cities: Cases Diverting the New National Capital - Nurcahya, Yan; Hambaliana, Dandie (Jurnal Ilmu Sosial dan Humaniora, 2025)
Sustainable development has become a mandatory concept in today's world of Architecture and Urban Planning. The Indonesian government plans to move the State Capital in this case the New State Capital (IKN), by shifting the state capital to Kalimantan. The government expects New IKN to become a city with sustainable urban development, apart from Jakarta as the main economic center in Indonesia. The new IKN development is expected to have a sustainable city concept, because building an area into a city is not only for now but can be used for our next nation.